2007
DOI: 10.3133/ofr20071090
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Concentrations in Middle Pennsylvanian Coal-Bearing Strata in the Central Appalachian Basin

Abstract: Appendix A1. Coal bed stratigraphy in core USGS 9 Appendix A2. Coal bed stratigraphy in core USGS 11 Appendix A3. Coal bed stratigraphy in core USGS 12 Appendix A4. Lithology terminology and abbreviations used by the West Virginia Geological and Economic Survey for core description Appendix A5. Geologists' description of core USGS 9 Appendix A6. Geologists' descriptions of core USGS 11 Appendix A7. Geologists' descriptions of core USGS 12 Appendix A8. Natural gamma ray, density, resistivity and caliper logs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Adams and Pennington (2005) and Renner (2005) have noted that mining operations and the subsequent processing and utilization of coal and minerals can result in the release of Se as oxyanions into wastewater and mine drainage. In streams impacted by surface coal mining in the central Appalachian basin, the Se concentration was higher (median 12 lg-Se/L) than that found in streams draining undisturbed areas (median 1.5 lg-Se/L) (Neuzil et al, 2007). Parida et al (1977), have found that Se can be present in four different oxidation states-selenide (Se 2 -), elemental selenium (Se 0 ), selenite (SeO 3 2 -), and selenate (SeO 4 2 -)-in aquatic environments.…”
Section: Introductionmentioning
confidence: 85%
“…Adams and Pennington (2005) and Renner (2005) have noted that mining operations and the subsequent processing and utilization of coal and minerals can result in the release of Se as oxyanions into wastewater and mine drainage. In streams impacted by surface coal mining in the central Appalachian basin, the Se concentration was higher (median 12 lg-Se/L) than that found in streams draining undisturbed areas (median 1.5 lg-Se/L) (Neuzil et al, 2007). Parida et al (1977), have found that Se can be present in four different oxidation states-selenide (Se 2 -), elemental selenium (Se 0 ), selenite (SeO 3 2 -), and selenate (SeO 4 2 -)-in aquatic environments.…”
Section: Introductionmentioning
confidence: 85%
“…In particular, mining operations and subsequent processing and utilization of coal and minerals can result in the release of Se as oxyanions into wastewater and mine drainage (Adams and Pennington, 2005;Renner, 2005). Se concentration in streams impacted by surface coal mining in the central Appalachian basin was higher (median 12 μg-Se/L) than streams draining the undisturbed areas (median 1.5 μg-Se/L) (Neuzil et al, 2007 (Sharmasarkar and Vance, 2002;Benjamin, 1983).…”
Section: Introductionmentioning
confidence: 91%
“…Selenium uptake through food is usually enough to meet human needs. ) (Parida et al, 1996) (Neuzil et al, 2007). In order to mitigate the negative impact, address the increasing public concerns, and meet the more stringent environmental regulations, removal of selenium from aqueous phase, either as selenate or selenite, has been a focus of many recent studies with an aim to develop cost-effective processes.…”
Section: Implication For Nutrient Removal From Municipal Wastewater Ementioning
confidence: 99%